Glycine-Histidine-Lysine (GHK) Alleviates Neuronal Apoptosis Due to Intracerebral Hemorrhage via the miR-339-5p/VEGFA Pathway - Zhang, Heyu (Front Neurosci, 2018)
Glycine-histidine-lysine (GHK) is a human tripeptide that enhances wound healing, exerts neuroprotective effects against neurodegenerative disease, and improves tissue regeneration. This study examined whether GHK can alleviate injury due to intracerebral hemorrhage (ICH). Briefly, adult Wistar rats in GHK pretreatment groups were injected with GHK (1 or 10 mg/kg, i.p.) every 24 h for 3 days. Water content and intact neurons were detected in the rats 3 days after ICH, and the neurological deficit scores were examined in the rats at 4, 24, 72, and 168 h after ICH. Apoptosis was evaluated via caspase-3 immunohistochemistry, Nissl staining, and TUNEL assay. We also examined the effect of GHK on the expression of related proteins in SH-SY5Y cells via Western blotting. The expression of miR-339-5p was examined via real-time polymerase chain reaction analyses. GHK improved neurological deficits, reduced water content in the brain and inhibited neuronal apoptosis in ICH rats. It also prevented the apoptosis of SH-SY5Y cells with hemin treatment. Furthermore, GHK downregulated miR-339-5p expression, and overexpression of miR-339-5p partially reversed the anti-apoptotic effects of GHK in SH-SY5Y cells. Our findings suggest that the p38 MAPK pathway is involved in the GHK-induced downregulation of miR-339-5p, and that the miR-339-5p/VEGFA axis plays a role in preventing neuronal apoptosis following ICH injury. These findings indicate that GHK may represent a novel therapeutic strategy for ICH.